Analysis Of Non-excusable Delay Factors Influencing Contractors' Performance In Lagos State, Nigeria - Ibironke, Olajide Timothy; Oladinrin, Timo Olugbenga; Adeniyi, Onaopepo; Eboreime, Idowu Victor (Penerbit Universiti Sains Malaysia, 2013)
Delays are one of the biggest problems faced by construction firms. The objectives of this study are to identify non-excusable delay factors, their effects on project completion and means of minimising these delays. A questionnaire survey was conducted to solicit the causes, effects and methods of minimising delays with two groups of respondents: consultants and contractors. Data were collected and analysed using a weighted mean method. A total of 57 major factors that cause non-excusable delays were identified from the reviewed literature and were further classified into eight major groups. The findings of this study revealed 20 key factors that cause non-excusable delays. The resultant effects of nonexcusable delays are time overrun, cost overrun and disputes, among others. Ensuring adequate financial sources, engaging competent project managers and making all necessary resources available are some of the most important means of minimising nonexcusable delays. Since non-excusable delays are specific to contractors, this study concludes that contractors should review their activities so that construction work will not be delayed.